新加坡小学生汉语时间副词“才、在、就”的使用偏误探析 = A study on the use of Chinese adverbs by Singaporean primary school English-Chinese bilingual students - 林雅诗 Lin, Yashi (2019)
关于汉语副词中的“才、在、就”在句子中的语法特征，许多学者都有所研究。然而较少学者关注汉语语言习得者对副词习得的情况，特别是中国境外普通话的汉语变体， 如新加坡华语的习得者是如何习得和使用汉语副词等。因此，本文以40名新加坡小五小六的学生作为研究对象，并通过调查问卷和测试的形式，考察了学生“才、在、就”的习得情况。其后，笔者将其偏误进行分析，并探讨造成这类偏误的原因。最后，笔者也提出了相关的教学建议。 本文的“才、在、就”偏误研究结果能帮助汉语语言教师进一步了解学习汉语的学生的习得情况，这对日后的“才、在、就”教学侧重点将有一定的指导意义。 Many scholars have done research on the Mandarin adverbs 才cái, 在zài, and 就jiù.. However, not many studies are found focusing on the acquisition of these adverbs, especially on the learners’ use of these adverbs outside of China, such as Singapore where a variety of Chinese, Singaporean Chinese is spoken. Thus, this thesis studied the acquisition of the above mentioned three adverbs in Chinese by 40 Singaporean Primary Five and Primary Six students. A questionnaire that include tests of the three adverbs were designed for data collection. The results were analyzed and discussed with a focus on misuses and the factors behind them. Lastly, suggestions on related pedagogies were given. It is hoped that this study will help Chinese language teachers to have a deeper understanding of the Chinese language acquisition by Singaporean bilingual children and be used as a useful reference for future research on related pedagogies.